Crossing the Line : A Look at the Symbols of the Ritual throughout Time - Otte, Jana Lynn (East Carolina University, 2014)
During the Age of Sail, sailors often marked their experience by the crossing of the equator or another Tropic line. This crossing indicated that the sailor had moved from the rank of inexperienced pollywog to the new rank of experienced shellback. The ceremony was, and still is, a rite of passage that led the sailors from one state to another, providing trials that helped move the sailors through the liminal phase between the two states of being. The symbolism inherent in the costumes, props, actions, and words can aid in modern understanding of this age-old tradition. This research looks at the symbolism involved in these rituals in order to achieve a better understanding of the meaning behind the rituals, while also applying the knowledge to modern day perceptions of the rituals in film, literature, and art.
Keywords: History; Ceremonies; Rituals; Sailors; Semiotics; Sailors--Social life and customs; Initiation rites; Shellbacks; Equator